The (not so) invisible hand: Perceptions of game designers and the impact on play - Young, Alyson Leigh; Lutters, Wayne (AoIR Selected Papers of Internet Research, 2013)
Designing and operating alternate reality games (ARGs) is always a challenge. Controlling too much or too little of the gameplay impedes player enjoyment. In studying one particular ARG, I Love Bees (ILB), and player perceptions of the game designers, we revealed that is possible for game designers relinquish direct control, but at a cost. Players often misread or misinterpreted game designers’ intentions. These issues, however, were not necessarily detrimental to gameplay and may have increased player enjoyment.